N′-(2-Hydroxy-5-nitrobenzylidene)benzenesulfonohydrazide - Yusnita, Juahir; Ali, Hapipah Mohd; Puvaneswary, Subramaniam; Robinson, Ward T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The molecule of the title compound, C13H11N3O5S, shows a phenyl group and an almost planar intramolecularly hydrogen-bonded N′-(2-hydroxy-5-phenylebenzylidene)hydrazino group disposed about the S atom. Adjacent molecules are linked by N—H⋯Onitro hydrogen bonds, producing a linear chain that runs along the b axis of the unit cell.